High-resolution paleolimnology opens new management perspectives for lakes adaptation to climate warming - Perga, Marie-Elodie; Frossard, Victor; Jenny, Jean-Philippe; Alric, Benjamin; Arnaud, Fabien; Berthon, Vincent; Black, Jessica; Domaizon, Isabelle; Giguet-covex, Charline; Kirkham, Amy; Magny, Michel; Manca, Marina; et al. (Frontiers in Ecology and Evolution, 2015)
Varved lake sediments provide opportunities for high-resolution paleolimnological investigations that may extend monitoring surveys in order to target priority management actions under climate warming. This paper provides the synthesis of an international research program relying on >150 years-long, varved records for three managed perialpine lakes in Europe (Lakes Geneva, Annecy and Bourget). The dynamics of the dominant, local human pressures, as well as the ecological responses in the pelagic, benthic and littoral habitats were reconstructed using classical and newly developed paleo-proxies. Statistical modelling achieved the hierarchization of the drivers of their ecological trajectories. All three lakes underwent different levels of eutrophication in the first half of the XXth century, followed by re-oligotrophication. Climate warming came along with a 2°C increase in air temperature over the last century, to which lakes were unequally thermally vulnerable. Unsurprisingly, phosphorous concentration has been the dominant ecological driver over the last century. Yet, other human-influenced, local environmental drivers (fisheries management practices, river regulations) have also significantly inflected ecological trajectories. Climate change has been impacting all habitats at rates that, in some cases, exceeded those of local factors. The amplitude and ecological responses to similar climate change varied between lakes, but, at least for pelagic habitats, rather depended on the intensity of local human pressures than on the thermal effect of climate change. Deep habitats yet showed higher sensitivity to climate change but substantial influence of river flows. As a consequence, adapted local management strategies, fully integrating nutrient inputs, fisheries management and hydrological regulations, may enable mitigating the deleterious consequences of ongoing climate change on these ecosystems.